Oden Cekyana: social media portfolio / Wardahtie Najieha Abdul Hamid, Nurhidayah Ahmad Sharifuddin and Norshafiqah Mohd Rahim - Abdul Hamid, Wardahtie Najieha; Ahmad Sharifuddin, Nurhidayah; Mohd Rahim, Norshafiqah (2021)
Oden Cekyana by HSW selling spices with variety of flavour. Our business is focus on steamboat and easy to cook within 5minutes. We are an agent from Odeen Viral Cekyana Hq. our business also have register under go-ecommerce. We are running online business through media social like facebook. We will ensure that our customer will satisfied with our food and services. This business is owned by three members, Hidayah, Shafiqah and Wardahtie. All partners will be taking hands on management roles in this business. Shafiqah and Wardahtie extensive experience in business and Hidayah has worked in sales and marketing for few years. We focused on audience that loves steamboat and people who don’t have many time to cook and who loves travels. Our business also provide services like cash on delivery, self-pickup and online postage. We put such a high hope that our business will growth and successful with all support from our beloved customer. We believe that knowledge that we have learned from this business will serve us well as we go forwards. The food and beverages industry have a great deal of opportunity but we also will faces some challenge as well. We feel that our business is in good position to growth and get higher profit in this industry.